Eye tracking technology on children's mathematical education: systematic review - Paskovske, Asta; Kliziene, Irina (Frontiers in Education, 2024)
Mathematical word problems are widely recognized as essential tools for assessing the practical application of mathematical knowledge among students. This study endeavours to ascertain the extent to which elementary school students' problem-solving skills have been investigated utilizing eye tracking technology and to elucidate the contribution of eye tracking technology in analysing students' problem-solving capabilities. To identify the prevailing themes within empirical research concerning the application of eye tracking methodology in the context of problem solving and mathematics, a systematic literature review was undertaken, following the guidelines outlined in the revised 2020 Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA). The initial search yielded 167 studies; however, after excluding studies that did not meet the predetermined inclusion criteria, a final selection of seventeen studies was made. Given the mounting interest in the intersection of eye tracking technology and mathematics education, this research has proven to be a valuable avenue for exploring students' problem-solving processes, comprehension strategies, and metacognitive abilities. Moreover, it offers valuable insights into the distribution of students' attention, their utilization of strategies, and their cognitive workload while engaged in problem solving tasks.